EXPLORING PERCEPTIONS ABOUT COGNITIVE SCREENING IN A RURAL APPALACHIAN COHORT. (11th November 2018) - Williams, C L; Wiese, L K; Williams, I; Galvin, J E
Abstract: The self-reliance that Appalachian residents are often known for can inadvertently create barriers to seeking much needed health services in this group, which includes a high percentage of older adults (21.3%) facing disproportionate dementia risk. Exploring a community's perceptions about cognitive screening is essential prior to offering routine screenings. The aim of this study was to examine if factors such as age, health literacy, and livelihood impacted attitudes toward routine cognitive screening in a rural Appalachian cohort. Researchers applied a parallel mixed method design of semi-structured interviews, measurements of health literacy (REALM-SF), sociodemographics, and cognitive screening perceptions (PRISM-PC), to examine beliefs and attitudes about memory screening among 22 WV rural stakeholders (residents, health providers, and administrators). Ninety-percent of study participants were highly favorable of earlier dementia detection through routine cognitive screenings, regardless of background. Rural providers and health educators are encouraged to consider routine cognitive screening for their patients.